Implicit and conventional large eddy simulation of flow around a circular cylinder at Reynolds number of 3900 - Li, Zhuoneng; Da Ronch, Andrea; Rana, Zeeshan A.; Jenkins, Karl W. (American Institute of Aeronautics and Astronautics (AIAA), 2024)
The implicit Large Eddy Simulation (iLES) incorporating an unstructured 3rd-order Weighted Essential Non-Oscillatory (WENO) reconstruction method and the conventional Large Eddy Simulation with Wall Adapting Local Eddy-Viscosity (WALE) are investigated on the flow around a circular cylinder at a Reynolds number of 3900. Simulations are carried out in the framework of open-source package OpenFOAM with a 2nd-order Euler implicit time integration and Pressure-Implicit Splitting-Operator (PISO) algorithm is used for the pressure-velocity coupling. The results are compared to the high fidelity experiment and DNS data, and demonstrated a favourable performance for iLES with a 3rd-order WENO scheme on the instantaneous flow structure. The conventional LES on the prediction of mean surface pressure coefficient and velocity profiles on the wake can be beneficial by reducing the effect of Rhie-Chow interpolation. The spectral analysis reveals that the current simulations are also capturing Von Karman shedding frequencies and shear layer frequencies. Finally, distinct features of iLES and LES are discussed.
Keywords: Pressure Drag Coefficient; Weighted Essentially Non Oscillatory; Boundary Layer Instability; Reynolds Averaged Navier Stokes; Kinematic Viscosity; Wall Adapting Local Eddy Viscosity; Spectral Analysis; Karman Vortex Street; Incompressible Flow; Aspect Ratio